An allergenic plant calmodulin from Artemisia pollen primes human DCs leads to Th2 polarization - Zhang, Yue; Hu, Wenzhi; Chen, Dongbo; Ding, Ming; Wang, Tao; Wang, Yaojun; Chi, Jiaoni; Li, Zhimin; Li, Qiang; Li, Chengxin (Frontiers in Immunology, 2022)
Artemisia pollen is the major cause of seasonal allergic respiratory diseases in the northern hemisphere. About 28.57% of Artemisia allergic patients’ IgE can recognize ArtCaM, a novel allergenic calmodulin from Artemisia identified in this study. Theses patients exhibited stronger allergic reactions and a longer duration of allergic symptoms. However, the signaling mechanism that triggers these allergic reactions is not fully understood. In this study, we found that extracellular ArtCaM directly induces the maturation of human dendritic cells (DCs), which is attributed to a series of Ca2+ relevant cascades, including Ca2+/NFAT/CaMKs. ArtCaM alone induces inflammatory response toward Th1, Th17, and Treg. Interestingly, a combination of ArtCaM and anti-ArtCaM IgE led to Th2 polarization. The putative mechanism is that anti-ArtCaM IgE partially blocks the ArtCaM-induced ERK signal, but does not affect Ca2+-dependent cascades. The crosstalk between ERK and Ca2+ signal primes DCs maturation and Th2 polarization. In summary, ArtCaM related to clinical symptoms when combined with anti-ArtCaM IgE, could be a novel allergen to activate DCs and promote Th2 polarization. Such findings provide mechanistic insights into Th2 polarization in allergic sensitization and pave the way for novel preventive and therapeutic strategies for efficient management of such pollen allergic disease.